Reduced IL-17A Secretion Is Associated with High Levels of Pneumococcal Nasopharyngeal Carriage in Fijian Children - Hoe, Edwin (PLoS One, 2015)
Streptococcus pneumonia (the pneumococcus) is the leading vaccine preventable cause of serious infections in infants under 5 years of age. The major correlate of protection for pneumococcal infections is serotype-specific IgG antibody. More recently, antibody-independent mechanisms of protection have also been identified. Preclinical studies have found that IL-17 secreting CD4+ Th17 cells in reducing pneumococcal colonisation. This study assessed IL-17A levels in children from Fiji with high and low pneumococcal carriage density, as measured by quantitative real-time PCR (qPCR). We studied Th17 responses in 54 children who were designated as high density carriers (N=27, >8.21x10(5) CFU/ml) or low density carriers (N=27, <1.67x10(5) CFU/ml). Blood samples were collected, and isolated peripheral blood mononuclear cells (PBMCs) were stimulated for 6 days. Supernatants were harvested for cytokine analysis by multiplex bead array and/or ELISA. Th17 cytokines assayed included IL-17A, IL-21, IL-22 as well as TNF-α, IL-10, TGF-β, IL-6, IL-23 and IFNγ. Cytokine levels were significantly lower in children with high density pneumococcal carriage compared with children with low density carriage for IL-17A (p=0.002) and IL-23 (p=0.04). There was a trend towards significance for IL-22 (p=0.057) while no difference was observed for the other cytokines. These data provide further support for the role of Th17-mediated protection in humans and suggest that these cytokines may be important in the defence against pneumococcal carriage.